Islam and Local Politics: In the Quest of Kyai, Politics, and Development in Kebumen, 2008-2010 - Laila Kholid Alfirdaus (Al-Jami'ah: Journal of Islamic Studies, 2013)
The involvement of kyai (religious teacher) in political affairs has become prominent after the Indonesia reformation. With his charismatic images and long-maintained religious authority, kyai has amount of capital to easily enroll his self into politics without significant barriers. This becomes more evidence in the Indonesian political sphere after the reformation as the number of kyais serving as leaders in bureaucracy is increasing. However, their inclusion in politics does not always lead to the birth of greater impact on public policy. During the leadership of kyai in the governmental body, Kebumen -as a case study discussed in this article- has experienced late development, indicated by lessening development in terms of public infrastructure and social services.[Keterlibatan kyai dalam politik muncul secara masif sejak bergulirnya reformasi. Dengan kharisma dan otoritas keagamaan, kyai memiliki modal penting untuk terjun dalam politik tanpa kendala berarti. Inilah yang menjadi sangat jelas terkait peran kyai dalam politik, utamanya dengan semakin banyaknya jumlah kyai yang menjabat sebagai pimpinan birokrasi. Sayangnya, keterlibatan mereka kerap tidak menyebabkan lahirnya kebijakan publik yang relevan. Pada masa pemerintahan kyai sebagai bupatinya, Kebumen -yang menjadi lokus tulisan ini- mengalami ketertinggalan dalam pembangunan. Ini setidaknya ditandai dengan semakin melemahnya infrastuktur publik dan pelayanan sosial.]